Late Oligocene fishes (Chondrichthyes and Osteichthyes) from the Catahoula Formation in Wayne County, Mississippi, USA - David J. Cicimurri; Jun A. Ebersole; Gary L. Stringer; James E. Starnes; George E. Phillips (European Journal of Taxonomy)
Isolated elasmobranch and teleost teeth, jaws, otoliths, scales, vertebrae, and fin spines were recovered from the upper Oligocene (Chattian) Catahoula Formation in Wayne County, Mississippi, USA. A total of 13 551 specimens were examined and 12 340 of these were identified at least to the ordinal level. These remains represent 49 unequivocal fish taxa, viz. 29 elasmobranchs and 20 teleosts. The 3614 elasmobranch remains indicate that Carcharhiniformes is the most diverse group of Elasmobranchii, with 12 taxa belonging to five families. Orectolobiformes and Lamniformes are represented by far fewer taxa (three and four, respectively). Carcharhinus acuarius (Probst, 1879) constitutes 49% of the total number of shark teeth in our sample. Ten batoids have been identified within Myliobatiformes (seven taxa) and Rhinopristiformes (three taxa). Partial teeth of durophagous myliobatids (three genera) are the most abundant batoid remains, constituting 41% of the total number of ray fossils. However, teeth of Dasyatidae and Rhynchobatus cf. pristinus (Probst, 1877) are abundant and represent 36.5% and 15.4%, respectively, of the specimens identified. Herein, we erect five new elasmobranch taxa, including Galeocerdo platycuspidatum sp. nov., Hemipristis intermedia sp. nov., Hypanus? heterodontus sp. nov., “Sphyrna” gracile sp. nov., and “Sphyrna” robustum sp. nov.